2011
DOI: 10.1002/hyp.7971
|View full text |Cite
|
Sign up to set email alerts
|

Lysimeter soil water balance evaluation for an experiment developed in the Southern Brazilian Atlantic Forest region

Abstract: Abstract:This study aims at monitoring the behaviour of the rainfall, runoff, drainage, soil water storage, and evapotranspiration variables involved in the water balance measured by lysimeter data. The evaluation of the water balance considered different time scales, where the components were monitored daily and in 10-day accumulated period intervals. The results demonstrated that in wet periods the soil water content was greater at a depth of 10 cm, whereas in the dry periods a greater concentration was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In native grass, the soil water storage varied between 94.48 and 244.30 mm, having an average of 155.57 mm. These results are in accordance with those published by Feltrin andPaiva (2009) and, Feltrin et al 2011, which were obtained in tensiometers that were installed at depths of 0.10, 0.30 and 0.70 m inside of a drainage lysimeter, and at the same place where the behavior of the soil water content, for grass native field was monitored.…”
Section: Resultssupporting
confidence: 92%
“…In native grass, the soil water storage varied between 94.48 and 244.30 mm, having an average of 155.57 mm. These results are in accordance with those published by Feltrin andPaiva (2009) and, Feltrin et al 2011, which were obtained in tensiometers that were installed at depths of 0.10, 0.30 and 0.70 m inside of a drainage lysimeter, and at the same place where the behavior of the soil water content, for grass native field was monitored.…”
Section: Resultssupporting
confidence: 92%
“…HYDRUS-1D (version 4.17) was used by Feltrin et al (2013) to simulate the dynamic of water in the soil, in an area under vegetation cover in a native field. Feltrin et al (2013) compared the simulated results with results obtained in field measurements; they concluded that the results presented by the program are compatible with the drainage obtained in a lysimeter.…”
Section: Hydrus-1d Modelmentioning
confidence: 99%
“…HYDRUS-1D (version 4.17) was used by Feltrin et al (2013) to simulate the dynamic of water in the soil, in an area under vegetation cover in a native field. Feltrin et al (2013) compared the simulated results with results obtained in field measurements; they concluded that the results presented by the program are compatible with the drainage obtained in a lysimeter. Zhang et al (2017) applied the SINMAP model to Zhouqu County, successfully identifying areas susceptible to landslides, and determined the saturated hydraulic conductivity for use in the model, using the HYDRUS-1D software.…”
Section: Hydrus-1d Modelmentioning
confidence: 99%
“…In order to achieve the optimal irrigation application and to maximize its efficiency, it is necessary to know the precise amount of water required by the crop for its specific development conditions [4,8]. These water requirements can be estimated accurately through a water balance, which quantifies the input and output flows of the soil profile in the crop root zone [8][9][10]; in addition, a water balance helps to reduce water losses and to diagnose the irrigation method itself [11].…”
Section: Introductionmentioning
confidence: 99%